The Role of Stakeholder Oriented Corporate Governance on Double Bottom Line Performance in Microfinance Institutions - Hossain, Shahadat (Curtin University, 2018)
This thesis examines the influence of internal and external governance mechanisms on double bottom line performance in microfinance institutions. As the internal governance mechanism, the thesis investigates the presence of founding directors, independent directors and employees on the board and their human and social capital attributes. As the external governance mechanism, the thesis examines competition in the market. The researcher uses Bangladesh data for the internal governance and cross-country data for the external governance study.